BUKU PANDUAN PENGKAFIRAN: Evaluasi Kritis TibyÄn fÄ« Maâ€™rifat al-AdyÄn karya NÅ«r al-DÄ«n al-RanÄ«rÄ« - Nasution, Ismail Fahmi Arrauf (Jurnal THEOLOGIA, 2018)
Abstract: The aim of this article is to critically evaluate the thought of NÅ«r al-DÄ«n al-RanÄ«rÄ«, particularly his thought in TibyÄn fÄ« Maâ€™rifat al-AdyÄn. The book contained his accusation of others as being a kafir. This Indian origin theologian explained the history of religions from the times of Adam to the times of Jesus. He claimed that those pre-Islamic religion had perverted. He discussed also Islamic theological schools such as Rafidi, Khawarij, Jabbariyah, Qadariyah, Jahmiyah, Murji'ah and Karamiyah. He said that those schools are perverted as well. According to him, only Ahl al-Sunnah wa â€™l-jamÄâ€™ah is the right theology. He also discussed various ideologies and the practices of mysticism that have ever grown and claimed that those are perverted too, except the akhlaqi tasawwuf. This article reviews the historical background of Aceh chronically till this "guidance book of takfir" come into existence. For that cause, the content of TibyÄn fÄ« Maâ€™rifat al-AdyÄnwill is discussed in brief. Finally, the theological thought of al-RanÄ«rÄ« regarding the unity of being. The article focuses on the criticism over the attack of al-RanÄ«rÄ« against the concept of the unity of being held by Hamzah FansÅ«rÄ« and Shams al-DÄ«n al-SumatranÄ«.Abstrak: Tulisan ini bertujuan melakukan evaluasi kritis atas pemikiran NÅ«r al-DÄ«n al-RanÄ«rÄ«, khususnya dalam bukunya TibyÄn fÄ« Maâ€™rifat al-AdyÄn. Dalam buku tersebut dia mengkafirkan banyak pihak. Teolog asal India itu mengulas sejarah agama-agama sejak Adam hingga Isa al-Masih. Dia mengatakan agama-agama tersebut telah menjadi agama yang sesat setelah Islam muncul. Selanjutnya dia membahas aliran-aliran teologi seperti Rafidi, Khawarij, Jabariyah, Qadariyah, Jamamiyah, Murjiâ€™ah dan Karamiyah. Dia mengatakan semua aliran teologi terÂsebut adalah sesat. Menurutnya aliran yang benar hanya Ahl al-Sunnah wa â€™l-JamÄâ€™ah. Selanjutnya dia mengulas berbagai itikad dan praktik mistisme yang pernah berkembang dan mengatakan semua itu sesat kecuali aliran tasawuf akhlaqi. Tulisan ini mengulas tentang latar belakang Aceh secara kronologis hingga â€œbuku panduan pengkafiranâ€ tersebut hadir. Selanjutnya diulas secara ringkan isi TibyÄn fÄ« Maâ€™rifat al-AdyÄn. Terakhir dilakukan evaluasi kritis atas pandangan teologis al-RanÄ«rÄ« tentang Waá¸¥dat al-WujÅ«d. Tulisan ini berfokus pada kritik atas serangan al-RanÄ«rÄ« terhadap pemikiran Waá¸¥dat al-WujÅ«d yang dipegang oleh Hamzah FansÅ«rÄ« dan Shams al-DÄ«n al-SumatranÄ«.